Comprehensive analysis of transcriptome characteristics and identification of TLK2 as a potential biomarker in dermatofibrosarcoma protuberans - Zhang, Xiao; Sun, Di; Zheng, Haiyan; Rao, Yamin; Deng, Yuqi; Liang, Xiao; chen, Jun; Yang, Jun (Frontiers in Genetics, 2022)
Background: Dermatofibrosarcoma protuberans (DFSP) is a rare cutaneous sarcoma characterized by local invasion and recurrence. RNA sequencing (RNA-seq) allows the qualification of cellular RNA populations and provides information on the transcriptional state. However, few studies have comprehensively analyzed DFSP transcriptional data. Methods: Fourteen DFSP samples with paired non-neoplastic soft tissue from Chinese patients undergoing Mohs micrographic surgery were used for RNA-seq analysis. Differential expression analysis and enrichment analysis for RNA-seq data were performed to identify fusion genes, biomarkers, and microenvironment characteristics of DFSP. Results: This study systemically describes the transcriptomic characteristics of DFSP. First, we performed gene fusion analysis and identified a novel FBN1-CSAD fusion event in a DFSP patient with fibrosarcomatous transformation. Then, we identified TLK2 as a biomarker for DFSP based on functional enrichment analysis, and validated its accuracy for diagnosing DFSP by immunohistochemical staining and joint analysis with public data. Finally, microenvironment analysis described the infiltration characteristics of immune and stromal cells in DFSP. Conclusion: This study demonstrates that RNA-seq can serve as a promising strategy for exploring molecular mechanisms in DFSP. Our results provide new insights into accurate diagnosis and therapeutic targets of DFSP.